The Education of Family Medicine Services Using Artificial Intelligence Video Method for Hypertension Prolanis Patients at Simpang Kawat Health Center. - Okta Arizki; Armaidi Darmawan; Ahmad Syauqy; Wahyu Indah Dewi Aurora; Esa Indah Ayudia (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Background: Hypertension management requires effective strategies, with family medicine often playing a neglected role. Objective: This study examines the efficacy of AI-based videos in improving knowledge among Prolanis hypertension patients at Simpang Kawat Health Center. Methods: This quasi-experimental study employed a pre-test post-test control group design. The experimental group (43 Prolanis hypertension patients from Simpang Kawat Health Center) received AI video education, while the control group (39 patients from Talang Bakung Health Center) received traditional slide-based education. Participants were selected via purposive sampling. Results: The majority of patients at Simpang Kawat Health Center were adults (55.8%), female (86%), and had primary education (44.2%). In contrast, most patients at Talang Bakung Health Center were elderly (76.9%), female (100%), and had primary education (74.4%). The knowledge level of hypertensive Prolanis patients at Simpang Kawat Health Center significantly improved after receiving AI-based video education, with the percentage of patients with low knowledge dropping from 88.4% to 41.9%. Similarly, at Talang Bakung Health Center, the standard education method led to an improvement, with the percentage of patients with low knowledge reducing from 87.2% to 60.5%. Conclusion: AI-based educational videos were more effective than traditional methods in enhancing patient knowledge.